The Effectiveness of Artificial Intelligence in Judicial Decision-Making in Indonesia - Hukom, Rafli; Martinus (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The advancement of artificial intelligence (AI) technology has brought significant transformations across various sectors, including the judicial system. Countries such as China and the United States have adopted AI in legal decision-making, whereas Indonesia remains in the early stages of implementing this technology. While AI has the potential to enhance judicial efficiency, challenges related to regulation, transparency, and algorithmic bias raise concerns regarding the accuracy and fairness of legal rulings. Therefore, this study aims to analyze the effectiveness of AI utilization in Indonesia’s judicial system, identify key challenges, and propose policy recommendations. This research employs both normative and empirical approaches by examining AI-related regulations and conducting interviews with judges and technology experts in Indonesia. The findings indicate that 65% of judges in Indonesia remain skeptical about AI's role in legal decision-making. In contrast, in countries like China, AI adoption in the judiciary has improved case resolution efficiency by 30–40%. Additionally, a public survey reveals that while 55% of respondents believe AI can enhance the objectivity of legal rulings, 45% remain concerned about potential algorithmic bias. Furthermore, the study highlights that Indonesia lacks specific regulations governing AI in the legal system, which may hinder the widespread adoption of this technology. This research contributes to understanding the readiness of Indonesia’s judicial system in integrating AI and emphasizes the necessity of clear regulations and robust oversight mechanisms to ensure transparency and accountability. The findings are expected to serve as a foundation for policymakers in formulating comprehensive regulations to optimize AI implementation in the Indonesian judicial system